Using Space Radiation Shielding Made of Polyethylene Instead of Aluminum in GEO Orbit to Reduce Weight - Pedram Hajipour; Leila mohammadi; Azam Eidi; Sara Shoorian; Nahid Eidi Esfiani; Seyed Amir Hossein Feghhi (فصلنامه علوم و فناوری فضایی, 2023)
One of the damaging factors for the proper functioning of telecommunication payloads are high energy ionizing particles in space, which the use of proper shield is a way to deal with it. In the design of protection, several factors, such as the type of part and the amount of weight acceptable for the payload.etc.must be taken into consideration. In recent years, in order to reduce the costs of construction and launch, the use of non-space components has been favored.Therefore, the use of shields with the suitable material in with radiation resistance, with respect to the weight budget considerations, will be one of the important challenges .In this paper, the aim is to investigate the methods of reducing the weight budget considering with respect to the radiation damage of ionizing dose. In this regard, a five-year technology development mission in the GEO orbit has been predicted, and the results of simulations and testing of aluminum and polyethylene shielding to check ionizing dose damage, according to the initial and reference weight budget, have been presented and compared. The analysis and evaluation of the test results using polyethylene protection shows a 17.21 percentage reduction between the two external and internal radiation meters.